(untitled) (Latakia University Journal -Engineering Sciences Series, 2017)
يتمحور العمل في هذا البحث حول تصميم مُناول روبوتي تسلسلي صناعييمتلك أربعدرجاتحرية (4-DOF) يقوم بأعمال المُناولة على خطوط الإنتاج وأعمال التوضيب للقطع الصغيرة،ويتميز بالمرونة وبإمكانية الانسجام مع الروبوتات الأخرى ضمن منطقة العمل. يوضّح البحث التوصيف الميكانيكي للمُناول ودراسة النموذج الحركي المباشر والنموذج الحركي العكسي بالإضافة إلى دراسة المسار. محركات المُناول الكهربائية هي محركات السيرفو (DC Servo motor). تصميم نظام القيادة الالكتروني للمُناول يستخدم شريحة الآردوينو (Arduino UNO). تُتيح الواجهة التطبيقية التخاطبية، التي تم بنائها ضمن البيئة البرمجية(Microsoft Visual Studio)،التحكُم بسهولة بالمُناولالروبوتي.حيث يحاكي نموذج المُناول الثلاثي الأبعاد (3D) حركته على أرض الواقع. يُناقش القسم الأخير من البحث نتائج اختبار النموذج التطبيقي للمُناول الروبوتيالذي قمنا بتصميمه وتنفيذه. This research is centered on design of a serial industrial manipulator with 4 degrees of freedom(4-DOF) in order to manipulation on production linesand packaging tasks of small pieces, it is characterized by flexibility and the possibility of compatibility with other robots in the work area. Research explains the Mechanical description of the manipulator and the study of the inverse kinematic and direct kinematics in addition to the study of the path of the manipulator.Manipulator electric engines are servo motors (DC Servo motor). The design of the electronic driving system of the robot depends on the Arduino Board(Arduino UNO). The application interface, which was built within the software (Microsoft Visual Studio), allows to easily control the manipulator.Where the robot three-dimensional model (3D) simulates the movement of the robot at work. In the latter part of the research we discussed practical prototype test results of the robotic manipulator that we have designed and implemented.